2007
DOI: 10.1007/s10856-007-3279-z
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of biphasic calcium phosphates/polycaprolactone composites by melt infiltration process

Abstract: Synthesis and characterization of material properties of biphasic calcium phosphates (BCP)/polycaprolactone (PCL) composites, which were obtained by melt infiltration of PCL using porous BCP bodies, were investigated. Using 70 vol.% of poly methyl methacrylate (PMMA) powder as a pore-forming agent, porous BCP bodies were obtained by pressure less sintering depending on the temperature. The porous bodies obtained showed interconnected, spherical pores about 200 microm in diameter. Densification of the pore fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…One way to avoid blocking the pores during polymer impregnation is to optimize the polymer infiltration process thereby preserving the porosity . Polymer coatings that have been assessed as toughening agents include poly lactic acid (PLA), poly(lactic‐co‐glycolic acid) (PLGA), poly‐ɛ‐caprolactone and polyvinyl alcohol (PVA) …”
Section: New Perspectives and Other Novel Applications To Improve Thementioning
confidence: 99%
See 1 more Smart Citation
“…One way to avoid blocking the pores during polymer impregnation is to optimize the polymer infiltration process thereby preserving the porosity . Polymer coatings that have been assessed as toughening agents include poly lactic acid (PLA), poly(lactic‐co‐glycolic acid) (PLGA), poly‐ɛ‐caprolactone and polyvinyl alcohol (PVA) …”
Section: New Perspectives and Other Novel Applications To Improve Thementioning
confidence: 99%
“…179 Polymer coatings that have been assessed as toughening agents include poly lactic acid (PLA), poly(lacticco-glycolic acid) (PLGA), poly-E-caprolactone and polyvinyl alcohol (PVA). 72,[180][181][182][183][184][185][186][187][188]…”
Section: Bcp For Osseointegration In Functionally Loaded Areasmentioning
confidence: 99%
“…A number of researchers have reported the use of polymer infiltration into bioceramic scaffolds to increase mechanical properties [35][36][37][38][39][40] . In these studies, bioceramic porous structures were immersed in molten polymer or solution to achieve infiltration of either the filaments or the entire structure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, importance has been attached to the PCL-matrix composite for load-bearing orthopedic applications [6,7], for PCL is key among biodegradable and essentially nontoxic polymer groups used in biomaterials research [8]. Recent research results indicated that the mechanical properties of HA= PCL composites were close to the regime of some cortical bones, making this composite a potential bone candidate for use in load-bearing applications [9].…”
Section: Introductionmentioning
confidence: 99%